2018
DOI: 10.4038/suslj.v16i1.7715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Nutrient Management on Green Pod Yield of Chilli (Capsicum annuum L.) cv MIPC-01

Abstract: A field experiment was conducted to study the effect of combined application of organic manures with recommended inorganic fertilizers (RIF) and to find out the best combination of applications on green pod yield of chilli cv. MIPC-01 (Mahailluppallama Kaludawali Selection). The following five treatment combinations viz. T1-No fertilizer (control plot), T2-100% RIF, T3-50% RIF + 15 t ha-1 cattle manure, T4-50% RIF + 15 t ha-1 cattle manure + 250 kg ha-1 partially burnt paddy husk, T5-50% RIF + 15 t ha-1 cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
2
4
2
Order By: Relevance
“…NPK elements are the foremost nutrients required for plant growth and yield but plants require other nutrients too for better crop production. This finding agreed with Imthiyas and Seran (2017), Prradhiepan et al (2018) and Seran (2018) who stated that the combined use of organic and inorganic mineral fertilizers results in high crop yield than inorganic fertilizer alone. In general, proper application of organic manure improves soil properties which result in better nutrient supply to crop.…”
Section: Marketable Fruit Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…NPK elements are the foremost nutrients required for plant growth and yield but plants require other nutrients too for better crop production. This finding agreed with Imthiyas and Seran (2017), Prradhiepan et al (2018) and Seran (2018) who stated that the combined use of organic and inorganic mineral fertilizers results in high crop yield than inorganic fertilizer alone. In general, proper application of organic manure improves soil properties which result in better nutrient supply to crop.…”
Section: Marketable Fruit Yieldsupporting
confidence: 91%
“…Further, most of chemical fertilizers mainly contain NPK but crop needs macro and micro nutrients for its better growth and development. Thus, combined use of chemical and organic fertilizers in soil amendments increases crop production (Olaniyi et al, 2010, Imthiyas andSeran, 2017;Prradhiepan et al, 2018) Organic manure improves the soil physical, chemical, biological properties and also it is an alternative source to the inorganic fertilizers. Further, it helps in improving public health and conservation of resources (Kurdali and Al-Shamma'a, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed no significant difference in the root length of chili plants under five different fertilizer treatments (Figure 1C). Root length is a crucial parameter in absorbing water and plant nutrients that essential for plant growth and (Prradhiepan et al, 2018). In this study, though no significant differences were observed among treatments in root length, plants grown under 100% OMF showed higher values.…”
Section: Plant Growthcontrasting
confidence: 48%
“…Biofertilizers promote plant growth and nutrient absorption from the soil, as well as strengthen crops against biotic and abiotic stress [13]. They have nitrogen fixation and phosphorus solubilizing bacteria beside plant growth promoters Pariari and Khan [14]. Khan, et al [15] reported that biofertilizers can positively affect seed germination, root growth, and nutrient absorption in several crops.…”
Section: Growth and Yield Performancesmentioning
confidence: 99%